A Bench-Top Machine for Oil Palm Mesocarp Separation (Journal of Tropical Resources and Sustainable Science (JTRSS), 2015)
Palm oil is rich in carotenoids and the major component of its glycerides is the saturated fatty acid palmitic. Because of its economic importance as high-yielding source of edible and technical oils, the oil palm is now grown as a plantation crop in most countries with high rainfall in tropical climates within 10 of the equator. The individual fruit ranging from 6 to 20 gm, are made up of an outer skin (the exocape), a pulp (mesocarp) containing the palm oil in a fibrous matrix; a central nut consisting of a shell (endocarp); and the kernel, which itself contains an oil, quite different to palm oil, resembling coconut oil (Poku, 2002). Nowaday in Thailand there is no small-scale suitable machine for farmers to separate palm mesocarp from palm nut. This research aims to develop a machine to separate palm fruit mesocarp to yield palm oil of better quality. The machine has four units, namely a mechanical power unit, feed unit, mesocarp milling unit, and discharge unit. The vital part is the mesocarp milling disc, which is the main report of this paper. There are three types of discs according to the surface typography under this study: 1) a disk with small holes and rectangular steel bars on the disk surface; 2) a disk with small holes, each with 1.2 centimeter diameter; 3) a disk with small holes and small steel items on the disk surface. It was found that the highest yield was obtained from the disk with small steel items and can separate mesocarp cleanly from the palm fruit.
Keywords: Palm mesocarp; separation; palm oil milling